Awareness on Stroke Among Adults in a Community of Jhapa - Shrestha, Sunita; Paudel, Krishna; Maharjan, Jamuna Laxmi; Niroula, Dikshya (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: A stroke is a medical emergency that occurs as a result of decreased blood supply or cessation of blood flow to the brain. Even though there are preventable risk factors still, it is one of the leading causes of disability worldwide. This study was carried out with the aim of assessing awareness of stroke among adults in a community.Method: A descriptive cross-sectional study was conducted among 106 adults in a community. Interview schedule was used to collect data by using self-developed structured questionnaire Data analysis was done using descriptive and inferential statistics in SPSS version 23Result: More than half 50.9% had an adequate level of awareness on meaning of stroke(70.8), risk factors of stroke (70.8%) identified hypertension followed by stress (67.1%) symptoms (84.0%) identified severe headache followed by dizziness (69.8%).However, inadequate knowledge was present on immediate management of stroke(0%), time period to take the person to the hospital(17.9)%).There was a statistical association between sex and level of awareness (p=0.027), as well as between occupational status and level of awareness (p=0.000).Conclusion: More than half of the respondents had adequate level of awareness regarding stroke despite of this, there is inadequate level of knowledge regarding the risk factors, preventive measures, the time period to take the person to the hospital, and complications associated with stroke. Which indicates need awareness program on stroke